2012
DOI: 10.1016/j.phytochem.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and biochemical characterization of three phosphoglycerate kinase isoforms from developing sunflower (Helianthus annuus L.) seeds

Abstract: Three cDNAs encoding different phosphoglycerate kinase (PGK, EC 2.7.2.3) isoforms, two cytosolic (HacPGK1 and HacPGK2) and one plastidic (HapPGK), were cloned and characterized from developing sunflower (Helianthus annuus L.) seeds. The expression profiles of these genes showed differences in heterotrophic tissues, such as developing seeds and roots, where HacPGK1 was predominant, while HapPGK was highly expressed in photosynthetic tissues. The cDNAs were expressed in Escherichia coli, and the corresponding pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…PGK proteins are evolutionary and structurally conserved enzymes that play a key role in cell metabolism (Watson et al ., ; Davies et al ., ; Szilagyi et al ., ; Troncoso‐Ponce et al ., ). In plants, at least two PGK isoforms occur in two different cellular compartments, one in the cytosol and one in chloroplasts (Shah and Bradbeer, ).…”
Section: Discussionmentioning
confidence: 97%
“…PGK proteins are evolutionary and structurally conserved enzymes that play a key role in cell metabolism (Watson et al ., ; Davies et al ., ; Szilagyi et al ., ; Troncoso‐Ponce et al ., ). In plants, at least two PGK isoforms occur in two different cellular compartments, one in the cytosol and one in chloroplasts (Shah and Bradbeer, ).…”
Section: Discussionmentioning
confidence: 97%
“…However, this latter assumption has not been thoroughly investigated to date. Subsequently, a second cytosolic PGK isoform from sunflower (Helianthus annuus) was cloned (Troncoso-Ponce et al, 2012), and in the Arabidopsis (Arabidopsis thaliana) genome, an additional putative PGK isoform with an N-terminal plastid/chloroplast localization signal was identified (Ouibrahim et al, 2014). The presence of two PGKs in the plastid/chloroplast could lead to specialization, so that one of them could be involved in photosynthesis and the other in glycolysis, which seems to be the case of GAPDH isoforms (Anoman et al, 2015).…”
mentioning
confidence: 99%
“…Specifically, PGK2 could mediate the transport of viruses to the chloroplast (Lin et al, 2007;Cheng et al, 2013). The in vitro regulation of some PGK isoforms has been studied (Troncoso-Ponce et al, 2012;Morisse et al, 2014). It has been shown that the chloroplastic isoform of Chlamydomonas reinhardtii could be light regulated by thioredoxins (Morisse et al, 2014).…”
mentioning
confidence: 99%
“…Transcripts of C 4 enzymes used by Wang et al ( 2009 ) and Calvin enzymes used by Reyes-Prieto and Troncoso-Ponce in dark reaction as well as their isoforms in S. bicolor, Oryza sativa, Z. mays , and Arabidopsis thaliana (Reyes-Prieto and Bhattacharya, 2007 ; Troncoso-Ponce et al, 2012 ) were downloaded from NCBI or Phytozome 9.1. Besides, Transcripts of three species, O. sativa, Z. mays , and A. thaliana , in relative to Calvin enzyme families collected in PMN ( http://www.plantcyc.org/ ) were downloaded from Phytozome 9.1.…”
Section: Methodsmentioning
confidence: 99%